Gene Ontology Tools: A Comparative Study - Muhammad Shahzad; Kamran Ahsan; Adnan Nadeem; Muhammad Sarim (Journal of Basic & Applied Sciences, 2015)
Gene ontology (GO) is a key initiative of bioinformatics to provide uniform description of gene product in different public databases. The GO project has initiated 3 (three) structured and organized controlled vocabularies (i.e. ontology) that describes gene products in term of cellular components, biological processes and functions in an independent of species. This resource saves lots of time and effort in finding information of any particular gene from different databases. Since 1998, many tools have been developed which at one end relieves the researchers to search particulars about gene products but at other end makes difficult to opt most appropriate tool for any certain investigation in gene ontology. Here we present the state-of-the-art web based GO tools currently used for biological ontologies. We adopt comparison methodology in conjunction with visualization capabilities and sources of annotation data. This paper considers three GO tools for the said purpose. In Visualization capabilities; Indented List, Node-link & tree and Zoomable capabilities of selected tools have been analyzed. In the data sources section; currently available sources for data annotation have been discussed. This review will facilitate potential users of the GO tools to select an appropriate tool for their need.